A Simple Staining Method for Increasing Sensitivity in Detection of Alkyl Sulfatase in Native Polyacrylamide Gels - Ashok Kumar, Venkatesh Chaturvedi* (Journal of Phytology, 2010)
SUMMARY To increase the sensitivity in detection of alkyl sulfatases in Native PAGE gels, we report here a simple staining method based on Coomassie brillent blue R 250. This method facilitates in detection of faint alkyl sulfatase bands which are otherwise difficult to visualize. Key words: Alkyl sulfatase, Colloidal coomassie, Polyacrylamide gel (PAG) <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-ansi-language: EN-SG; mso-fareast-language: EN-SG; mso-no-proof: no;" lang="EN-SG">A Simple Staining Method for Increasing Sensitivity in Detection of Alkyl Sulfatase in Native Polyacrylamide Gels. J Phytol 2/6 (2010) 34-36